Neural networks with robust backpropagation learning algorithm - Walczak, B. (Analytica chimica acta, 1996)
A robust error suppressor function, which is independent of the underlying probability density function and convenient for computer programs, is proposed to robustify the backpropagation learning algorithm of multilayer feedforward networks. Its performance is studied for simulated data sets.